Human immune response to Phlebotomus sergenti salivary gland antigens in a leishmaniasis-endemic focus in Iran. (17th August 2020) - Veysi, Arshad; Mahmoudi, Ahmad Reza; Yaghoobi-Ershadi, Mohammad Reza; Jeddi-Tehrani, Mahmood; Rassi, Yavar; Zahraei-Ramazani, Alireza; Hosseini-Vasoukolaei, Nasibeh; Zareie, Bushra; Khamesipour, Ali; Akhavan, Amir Ahmad
ABSTRACT: Salivary proteins specific antibodies have been shown to be useful biomarkers of exposure to sand fly bites. This study aimed to investigate the level, duration, and dynamics of the human immune response against the SGL of Phlebotomus sergenti Parrot, 1917 (Diptera: Psychodidae), and to assess the immunoreactivity of human sera with SGL components in an endemic area of anthroponotic cutaneous leishmaniasis (ACL) in Iran. The study was carried out in 2-phase; longitudinal and cross-sectional. Sand flies were collected monthly from indoors and outdoors. In the longitudinal study, sera from healthy volunteers were collected monthly, and in the cross-sectional study, sera from healthy volunteers and patients with ACL lesion/s, were collected for immunoassay studies. The level of anti- P. sergenti saliva IgG was detected using the ELISA. Immunoreactivity of individual human sera with saliva components was also assessed by western blotting. Phlebotomus sergenti was the predominant sand fly species in the study area. The maximum and minimum percentages of IgG responses were seen in October (66%) and March (29%), respectively. Additionally, the cross-sectional study showed that 59.3% of the healthy volunteers and 80% of the patients were IgG positive. The antibody response against P. sergenti salivary gland was high during the sand fly active season and declined by the end of the activity of the vectors. Antibody response against the SGL components of P. sergenti was transient and individual-specific. Some individuals shared a strong reaction against certain individual antigens, which could be considered as vector exposure markers for further investigation. List of abbreviations: ELISA: Enzyme-Linked Immunosorbent Assay; SDS PAGE: Sodium Dodecyl Sulfate–Polyacrylamide Gel Electrophoresis; SGL: Salivary Gland Lysate; ACL: Anthroponotic Cutaneous Leishmaniasis; PBS: Phosphate Buffered Saline; BCA: Bicinchoninic Acid; PBS-T: Phosphate Buffered Saline Tween; FBS: Fetal Bovine Serum; HRP: Horseradish Peroxidase; TMB: 3, 3′, 5, 5′-Tetramethylbenzidine; PVDF: Polyvinylidene Difluoride; SGA: Salivary Gland Antigens; OD: Optical Density; KDa: Kilodalton; VL: Visceral Leishmaniasis; CL: Cutaneous Leishmaniasis; SGs: Salivary glands GRAPHICAL ABSTRACT: The antibody response was transient to P. sergenti salivary gland antigens, and some individuals shared a strong reaction toward some proteins of SGL.